Hubungan suhu tubuh dengan derajat Dangue Haemorragic Fever di Instalasi Gawat Darurat - Erviana, Kharisma Yuni; Maghfiroh, Isni Lailatul; Susanti , Inta (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: The severity of Dengue Hemorrhagic Fever (DHF) can be influenced by various clinical factors, including platelet count, body temperature, and duration of fever. Early identification of these factors is crucial to prevent severe complications such as bleeding and shock. This study aims to examine the relationship between platelet count, fever duration, and body temperature and the severity level of DHF in patients treated at the Emergency Department of Muhammadiyah Islamic Hospital, Sumberrejo. Methods: This research used a retrospective analytic design based on secondary data from patient medical records. A total of 216 DHF patients were selected using consecutive sampling. Result: Data were analyzed using the Spearman correlation test. The results showed that 92.6% of patients had a platelet count of <100,000/mm³, 49.1% experienced fever for 4–5 days, and 76.4% had a body temperature above 39°C. Most patients (57.9%) were classified as having DHF Grade 3. Conclusion: Statistical analysis revealed a significant correlation between all variables (p = 0.000), with correlation coefficients of -0.436 for platelet count, 0.401 for fever duration, and 0.482 for temperature. These results indicate a moderate correlation between each variable and the severity level of DHF. Specifically, lower platelet counts, higher body temperature, and longer fever duration are associated with more severe DHF grades.